Dynamic Control of Speed and Trajectories of Active Droplets in a Nematic Environment by Electric Field and Focused Laser Beam - Rajabi, Mojtaba; Baza, Hend; Wang, Hao; Lavrentovich, Oleg D. (Frontiers in Physics, 2021)
One objective of active matter science is to unveil principles by which chaotic microscale dynamics could be transformed into useful work. A nematic liquid crystal environment offers a number of possibilities, one of which is a directional motion of an active droplet filled with an aqueous dispersion of swimming bacteria. In this work, using the responsiveness of the nematic to the electric field and light, we demonstrate how to control the direction and speed of active droplets. The dielectric response of nematic to the electric field causes two effects: (i) reorientation of the overall director, and (ii) changing the symmetry of the director configuration around the droplet. The first effect redirects the propulsion direction while the second one changes the speed. A laser beam pointed to the vicinity of the droplet can trigger the desired director symmetry around the droplet, by switching between dipolar and quadrupolar configurations, thus affecting the motility and polarity of propulsion. The dynamic tuning of the direction and speed of active droplets represents a step forward in the development of controllable microswimmers.